BRONZE MORTARS FROM THE COLLECTION OF THE STATE MUSEUM OF HISTORY OF UZBEKISTAN - Norkobilov, Tokhir (PT. Antis International Publisher, 2025)
Objective: This study investigates a small collection of medieval bronze mortars preserved in the State Museum of History of Uzbekistan to understand their historical significance, functional use, and regional similarities. Method: A comparative analysis was conducted to examine the morphological forms, decorative designs, and functional attributes of the mortars in relation to similar artifacts from Central Asia and neighboring countries. Results: The findings reveal striking similarities in the design and decoration of the mortars from the museum's collection with those from other regions. The mortars served various purposes, including use in production processes, daily life, and pharmacy. Most of the studied artifacts date back to the XI-XII centuries, with some extending to the XIV-XV centuries. Novelty: This research provides a focused examination of a specific collection, contributing to a deeper understanding of the shared cultural and functional aspects of bronze mortars across Central Asia during the medieval period.